2014
DOI: 10.1038/ncomms4521
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of separate predation- and defence-evoked venoms in carnivorous cone snails

Abstract: Venomous animals are thought to inject the same combination of toxins for both predation and defence, presumably exploiting conserved target pharmacology across prey and predators. Remarkably, cone snails can rapidly switch between distinct venoms in response to predatory or defensive stimuli. Here, we show that the defence-evoked venom of Conus geographus contains high levels of paralytic toxins that potently block neuromuscular receptors, consistent with its lethal effects on humans. In contrast, C. geograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
373
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 270 publications
(394 citation statements)
references
References 42 publications
20
373
0
1
Order By: Relevance
“…Extending our recently developed hypothesis that defensive venoms in vermivorous cone snails are repurposed for mollusc-and fish-hunting [8], we propose that defensive d-conotoxins were originally used by ancestral worm-hunting cone snails to protect against threats such as cephalopod and fish predation, and have been repurposed for fish-hunting in piscivorous Conidae. This finding has important implications for the diversification of diet in cone snails, with defensive d-conotoxins providing a molecular basis facilitating the shift from a diet of worms to fishes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extending our recently developed hypothesis that defensive venoms in vermivorous cone snails are repurposed for mollusc-and fish-hunting [8], we propose that defensive d-conotoxins were originally used by ancestral worm-hunting cone snails to protect against threats such as cephalopod and fish predation, and have been repurposed for fish-hunting in piscivorous Conidae. This finding has important implications for the diversification of diet in cone snails, with defensive d-conotoxins providing a molecular basis facilitating the shift from a diet of worms to fishes.…”
Section: Discussionmentioning
confidence: 99%
“…While these studies provide a mechanistic insight into the evolution and diversification of cone snail venom, they failed to identify a specific evolutionary path that drove the evolution of piscivory in cone snails. Unexpectedly, it was recently reported that cone snails can inject distinct venoms in response to predatory or defensive stimulus [8]. To this end, the venom gland is divided into two main parts, with the distal part producing conotoxins involved in prey capture, whereas the proximal section produces defensive conotoxins.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have long been focused on the venom of both fish-and mollusc-hunting cone snails due to the biomedical interest of the conopeptides of these species [30][31][32][33][34]. On the other hand, worm-hunting species have been rarely studied, even if recent studies have reported a variety of novel conopeptides, some of them with potent neuropharmacological activity present only in vermivorous cone snails [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Third, some of the conotoxin genes in the genome may not be expressed because they are no longer functional and have become psuedogenized. Finally, conotoxin gene expression may be regulated by defensive strategies against predators, as cone snails have been documented to release different conotoxins based on differing external stimuli (presentation of a prey item vs. physical agitation through poking, Dutertre et al 2014). However, this hypothesis remains to be tested as there exists no ecological information to suggest that cone snails use their venom for defense-observations in the literature show that often, cone snails will hide in their shell or become completely devoured when confronted with an aggressor (Kohn 1959b).…”
Section: Conotoxin Molecular Evolutionmentioning
confidence: 99%